Extremos climáticos de precipitação e a urbanização em Belém-PA - CIRINO, Luciana dos Santos (2019)
Aims to analyze the climatic variability linked topossible anthropogenic and natural effects, observed from the meteorological variables of air temperature (average, minimum and maximum) and precipitation on annual range for Amazonian metropolis of Belém. This metropolis has presented high population growth, greater social and economic prominence in the Amazon region. There fore, the importance of conducting this research focuses on the investigation of climatic extremes that has been the target of thee ffects caused by global climate change and affecting the socio-economic developmentof the population. For this we used monthly rainf all and temperature data for the period 1973 to 2015, provided by INMET, population data from 1992 to 2006 provided by IBGE and IOS data from NOAA for the period 1968 to 2015 applied to obtain the average social and environmental variability. And from this, performing the analysis of the data using the SPI.The results obtained based on climatologica studies for the months of January to May show the highest accumulated rainfall, being March the highest ammount, due to the effects of the ITCZ. However, it is worth mentioning that with the increase in population over the years that contributes to the uncontrolled urban growth, where the natural surfaces are replaced by artificial constructions, changing the pattern of cloudiness and consequently the increase in precipitation and maximum and minimum temperatures in the metropolis. It was observed that smaller annual accumulated precipitation occurred in 1983 with 2315mm, characterized by an El Niño episode 82/83 (IOS negative), and maximum in 2013, with 3773 mm, with a La Niña (IOS positive). The annual precipitation anomalies show a tendency of increase in annual precipitation, starting in the 90s and on, that agree with the period of population increase. Possibly the biggest man-made effect can be evidenced by the maximum and minimum temperatures every six months (less rainy and rainy seasons) that revealed an increase and decrease in amplitude over the years, respectively. This should be related to land use changes that causes changes in the radiation balance and consequently in the hydrological cycle. We hope that this study can corroborate with the knowledge of natural and anthropogenic effects observed in the metropolis, and enable information for urban planning and social.